A robust solvothermal-driven solid-to-solid transition route from micron SnC2O4 to tartaric acid-capped nano-SnO2 anchored on graphene for superior lithium and sodium storage. Issue 1 (6th December 2022) - Xie, Furong; Zhao, Shiqiang; Bo, Xiaoxu; Li, Guanghui; Fei, Jiamin; Ahmed, Ebrahim-Alkhalil M. A.; Zhang, Qingcheng; Jin, Huile; Wang, Shun; Lin, Zhiqun
Abstract : A robust solvothermal-driven solid-to-solid transition strategy is developed to craft tartaric acid-capped ultrafine SnO2 encapsulated in graphene with outstanding lithium and sodium storage reversibility due to effectively inhibited Sn coarsening. Abstract : Tin dioxide (SnO2 ) has been widely implemented as an advanced anode material for lithium or sodium ion batteries (LIBs/SIBs) owing to its high capacity and moderate potential. However, conventional synthetic approaches often yield large-sized SnO2, which suffers from low conductivity, huge volume expansion and Sn coarsening issues, hampering its practical implementation. Herein, a unique solvothermal-driven solid-to-solid transition (SDSST) strategy is developed to craft tartaric acid (TA) capped ultrafine SnO2 nanoparticles (NPs) in situ on sacrificial SnC2 O4 microrods. Ball-milling combined with solvent evaporation treatment realizes the homogeneous composition and precise mass ratio control of TA-capped SnO2 NPs and reduced graphene oxide (rGO). Remarkably, the SnO2 NPs-rGO nanocomposite manifests outstanding lithium and sodium storage capacities of 1775 and 463 mA h g −1 after 800 and 100 cycles at 1000 and 20 mA g −1, respectively, and an ultralong lifespan of 4000 cycles for LIBs. Notably, systematic electrochemical and componential characterization of the cycled electrodes reveals that SnO2 NPs-rGO manifests fully reversible three-step lithiation–delithiation reactions of SnO2 and a primary highly reversible sodiation–desodiation conversion reaction between Sn and SnO combined with a secondary partially reversible alloying–dealloying reaction between Sn and Na x Sn (0 ≤ x ≤ 3.75) for lithium and sodium storage, respectively. The even encapsulation of TA-capped SnO2 NPs in the rGO matrix enables effectively suppressed volume expansion for outstanding structural stability, significantly accelerated ion/electron transport for superior reaction kinetics, greatly prohibited Sn coarsening for enhanced cycle reversibility, and dramatically increased capacitive capacity for additional energy storage. As such, the SDSST approach may represent a facile yet robust strategy for crafting a variety of nanomaterials of interest with appropriate metastable solids as the precursor under the assistance of efficient capping agents.